The study of information system to transmit And store x-ray and ultrasound images - Tran, Thi Thu Ha (2020)
The health sector, everywhere in the world creates and processes vast amounts of data, primarily including patient data based on their history, the types of illnesses he / she has, and the result. Actual result of the drug. Most of the data is occupied by image data / generated from X-rays, ultrasound, etc. After storing it to the database. Managing or handling this big data is a serious problem. 90% of the data is image data generated by radiography and ultrasound and should be stored for further use in diagnostic processes, as well as for research. This data is like wine that has grown in strength over time. After much research, the name has been put into the picture, the Image Storage and Communication System (PACS) can meet all medical imaging issues as well as economic requirements. PACS is a network of computers for storing, retrieving, distributing and displaying images and medical data related to it. It is capable of processing different types of images from medical devices such as ultrasound, X-ray, etc. This article discusses the situation o f the healthcare industry with the implementation of PACS and related issues.